A hybrid model to analyze stress distributions at the tool and workpiece interface during drilling of thick cfrp laminates considering thermal effects - Shariar, Fahim; Karaguzel, Umut; Karpat, Yigit (SPRINGER LONDON LTD, 2025)
Drilling is employed as a machining method to meet the demands for producing functional CFRP structures without compromising their unique and desirable material properties. Because of its intrinsic material properties and drill-induced damages, drilling CFRP remains an ambitious task. This study investigates the stress distributions at the tool-workpiece interface during the CFRP dry drilling process. A better understanding of contact pressure and tangential stress distribution on the cutting edge of drills is necessary for a better selection of process parameters. The drill margin region, which directly affects the hole wall quality, has been included in the analysis. Drilling experiments were conducted to measure thrust force, torque, and temperature for different cutting parameter configurations. Finite element-based thermal models have been utilized to estimate the hole wall surface temperature during drilling. The analytical cutting force model is coupled with the temperature distribution from the FE model to analyze the variation of contact pressure and tangential stress distributions along the tip of the drill, together with the thermal effects on contact pressure during drilling.
Keywords: Drilling; Stress distributions; Polycrystalline diamond (PCD); Fiber reinforced polymer (FRP); FIBER-REINFORCED POLYMER; THRUST FORCE; TEMPERATURE; UD; PREDICTION; COMPOSITES; SIMULATION; Automation & Control Systems; Engineering